The No. 3 Craniofacial Cleft - - Sagiran (Universitas Muhammadiyah Yogyakarta, 2002)
Sumbing no.3 merupakan satu di antara 14 tipe kelainan sumbing kraniofasial kongenital. Lokasi sumbing ini bertepatan dengan tempat pertemuan antara proces¬sus maxillaris dan frontonasalis pada masa perkembangan embryonal. Mengetahui embryologi leher dan kepala memberi pemahaman mengenai fungsi saraf kepala, prinsip-prinsip pembentukan kepala-wajah dan kelainan-kelainannya yang merupakan akibat penyimpangan dari perkembangannya. Penanganan kelainan ini memerlukan bedah rekonstruksi yang canggih. Makalah ini melaporkan kasus seorang anak perempuan 1,5 tahun dengan sumbing kraniofasial no 3.The No. 3 Cleft is one of 14 types of congenital craniofacial cleft anoma¬lies. The location of no. 3 cleft coincides with the embryonic junction of the maxillary and frontonasal processes. There is no theory of the causes but some hypothetic risk factors have been proposed. Understanding of head and neck embryology gives rationale to the function of the cranial nerves, prin¬ciples of craniofacial form, and anomalies that result from aberrations in their development. Treatment of this malformation needs excellent reconstructive surgery. This paper is reporting a case of the no. 3 craniofacial cleft in a 1.5- year-old female.